Analysis of Occupational Health and Safety Firefighters in Makassar City - Basri Rakhman; Indra Wijaya; Imam Adrian Rakhman; Sintia Yulianti (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
The problems discussed in this study relate to the number of employee work accidents that tend to increase each year significantly due to aspects of the work environment, work equipment and materials, and how to do work. Therefore, this study's purpose of identifying and analyzing employees' occupational health and safety at the Makassar City Fire Department. The research method used is descriptive-quantitative. The population in this study were all firefighters in the Makassar City Fire Department, with a total sample of 214 people. Data collection techniques used in this study were questionnaires, observations, interviews, and document review using a Likert's Summated Rating (Likert's) scale analysis and SPSS 17 program assistance. The results showed that the occupational health and safety of the Makassar City firefighter department is a positive category. In addition, 196 respondents or 91,5% positive outlook and 18 respondents or 8,41% have a very positive outlook in environment work, 133 respondents or 37,9% positive outlook and 81 respondents or 37,9% positive outlooks about work equipment and materials. The last aspect shows 135 respondents or 63,1% positive outlooks and 79 respondents or 36,9% positive outlook on how to do the work